Contribution to regulatory science and a next challenge of the Japanese Environmental Mutagen Society (JEMS). (December 2016) - Uno, Yoshifumi
Abstract Many members of The Japanese Environmental Mutagen Society (JEMS) have significantly contributed to guidelines on chemical genotoxicity. The guidelines have been useful for the hazard identification and risk assessment of genotoxic chemicals. However, risk assessors and developers of drugs and other commercial products might eliminate beneficial chemicals from further development simply based on positive results of genotoxicity testing. Experts in the field of genotoxicity should better characterize the biological significance of genotoxicants and more correctly assess human risk. I hope that one of the next challenges undertaken by JEMS will be to assess the human risk of genotoxic chemicals more correctly based on the precise analysis of their mechanisms of action.